Epidemiologic case investigation on the zoonotic transmission of Staphylococcusaureus infection from goat to veterinarians. (5th May 2021) - Piva, Silvia; Mariella, Jole; Cricca, Monica; Giacometti, Federica; Brunetti, Barbara; Mondo, Elisabetta; De Castelli, Lucia; Romano, Angelo; Ferrero, Irene; Ambretti, Simone; Roccaro, Mariana; Merialdi, Giuseppe; et al.
Abstract: Staphylococcus aureus infection led to a case of goat abortion, and four veterinarians contracted S. aureus infection from the goat during and after the abortion. Three veterinarians assisted a doe during the dystocic delivery of a dead foetus. Seventy‐two hours after the dystocia, which ended with the goat's death, the veterinarians who assisted during the kidding and the veterinarian who performed the necropsy showed the presence of multiple, isolated, painful pustules 1–5 mm in diameter located along their forearms and knees. S. aureus was isolated from the pustules of the veterinarians, the placenta and uterus of the goat, the organs (brain, thymus gland, abomasum, liver and spleen) of the foetus, the scrotum and eye swabs of the buck, and mammary pustules of another goat from the same herd. Histological analysis revealed purulent metritis and inflammation of the placental cotyledons. Additional investigations eliminated the chances of other infections. S. aureus isolates recovered from the veterinarians, goats, foetus and buck were sensitive to the tested anti‐microbials and did not encode staphylococcal enterotoxin genes ( sea, ser, sep, see, seg and sei ). The isolates were closely related, as indicated by the results of Fourier‐transform infrared spectroscopy and comparative whole‐genome sequencing analysis. The results of this study clearly support the hypothesis that an episode of professional zoonosis was caused by S. aureus infection during the abortion and also highlight the need for bacterial subtyping in epidemiological surveys.